Drinking biodiversity: a choice experiment on Franciacorta sparkling wines. Issue 8 (11th March 2020) - Ruggeri, Giordano; Mazzocchi, Chiara; Corsi, Stefano
Abstract : Purpose: Consumers' concerns about the environmental impacts of food production have been increasing over the last years, and several certification systems for environment-friendly food products have been created. This research investigates wine consumers' preferences for a certification that guarantees the use of agricultural practices that better protect the biodiversity in the vineyard during the production of grapes. Design/methodology/approach: Using a choice experiment, we investigate consumer preferences and willingness to pay for biodiversity-friendly wines on a sample of 334 wine consumers. The experiment was carried out by direct interviews at a wine-tasting event in an Italian winery located in the Franciacorta area, in northern Italy. A between-subject design and two different questionnaires were used, one presenting the Brut bottle and one the Satén bottle. Findings: Estimates from a mixed logit model reveal that consumers are generally willing to pay a higher price for biodiversity-friendly wines, but they have stronger preferences for organic certification and quality indications. When consumers perceive a specific product as having high quality, i.e. Satèn, they might be less willing to pay for further environment-friendly certifications. Moreover, preferences depend on sociodemographic and attitudinal variables such as gender, wine consumption frequency, wine education and knowledge degree of the labels. Originality/value: This paper broadens the knowledge about consumer preferences and willingness to pay for biodiversity-friendly wines, focusing on a specific market segment of Italian sparkling wines.